1998
DOI: 10.1063/1.121425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ultraviolet light during rapid thermal diffusion

Abstract: Impact of metal silicide precipitate dissolution during rapid thermal processing of multicrystalline silicon solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is also possible that the ultraviolet (UV)/vacuum ultraviolet (VUV) radiation from the plasma or the synergy of impinging ions and UV/VUV radiation assists with oxygen diffusion. 26…”
Section: Ion-enhanced Diffusion Of Oxygen Through the Surface Oxidmentioning
confidence: 99%
“…It is also possible that the ultraviolet (UV)/vacuum ultraviolet (VUV) radiation from the plasma or the synergy of impinging ions and UV/VUV radiation assists with oxygen diffusion. 26…”
Section: Ion-enhanced Diffusion Of Oxygen Through the Surface Oxidmentioning
confidence: 99%
“…2 Experimentation with a combination of incandescent and mercury vapor lamps has indicated an increase in dopant diffusion under ultraviolet illumination. 3 Formation of shallow junctions from phosphorus surface diffusion was found to be affected also by exposure to vacuum ultraviolet photons (wavelength k < 200 nm). 4 Photonic effects have been studied in a variety of annealing experiments, 5,6 including the electrical activation and diffusion of n-type dopants in crystalline silicon.…”
Section: Introductionmentioning
confidence: 98%
“…This allows well-defined processing at elevated temperatures even for extremely short duration times in the range of a few seconds. Furthermore, several authors have observed an acceleration of diffusion and oxidation processes which they attribute to the significant proportion of high energy photons contained in the incident electromagnetic spectrum [1][2][3]. In summary these advantages account for a reduction in the total process time from 10 3 s down to 10 1 s, that is of about two orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%